The Effect Of Job Satisfaction And Employee Engagement On Turnover Intention With Organization Commitment As A Mediating Variable - Saputra, M. Rafikhansa Dzaky; Waskito, Jati (Jurnal Economic Resource, 2025)
In an effort to achieve quality human resources, organizational management needs to provide various supporting aspects that include policies related to employee turnover. So that through this study the company can get results from the influence of job satisfaction and employee engagement on turnover intentions with organizational commitment as a mediator, the distribution was carried out using quantitative methods and purposive sampling then obtained a total of 105 respondents with all of them being employees of the Dr. Ario Wirawan Lung Hospital (RSPAW) in Salatiga. Furthermore, the findings obtained in the form of Employee Engagement and Job Satisfaction cannot provide a significant influence on Turnover Intention. while other values stated that job satisfaction and employee engagement can provide a significant influence on organizational commitment. However, the mediation provided by organizational commitment has an insignificant influence on job satisfaction and employee engagement on turnover intentions